Colo-urachal fistula with infected urachus; a rare fate of urachus in adults - Samina Gohar; Jamaluddin, Muhammad; Rifsha Khalid (Journal of the Pakistan Medical Association, 2026)
Colourachal abnormalities are conditions that occur due to defective obliteration of urachus into the median umbilical ligament during the developmental period. The case of a middle-aged male who presented multiple times with recurrent abdominal pain, vomiting, and intermittent bloody loose stools is presented. On final admission, he developed signs of acute abdomen. Despite multiple visits, his workup remained inconclusive. Explorative laparotomy was performed which showed Colo-urachal fistula with infected urachus from which air was released upon incision and pus drained. The patient underwent a loop ileostomy, left hemicolectomy, and colocolic anastomosis. This case signifies the complexities of diagnosing and managing colo-urachal fistulas in adults. Keywords: Urachal Disorders, Laparotomy, Abdominal pain, Colectomy, Peritoneal Diseases, Fistula, Anastomosis, Ligaments, Suppuration.